Subject 01: exemplary Indigenous masculinity in Cold War genetics - DENT, ROSANNA (The British journal for the history of science, 2020)
In 1962 a team of scientists conducted their first joint fieldwork in a Xavante village in Central Brazil. Recycling long-standing notions that living Indigenous people represented human prehistory, the scientists saw Indigenous people as useful subjects of study not only due to their closeness to nature, but also due to their sociocultural and political realities. The geneticists’ vision crystalized around one subject – the famous chief Apöwẽ. Through Apöwẽ, the geneticists fixated on what they perceived as the political prowess, impressive physique, and masculine reproductive aptitude of Xavante men. These constructions of charismatic masculinity came at the expense of recognizing how profoundly colonial expansion into Mato Grosso had destabilized Xavante communities, stripping them of their land and introducing epidemic disease. The geneticists’ theorizing prefigured debates to come in sociobiology, and set up an enduring research programme that Apöwẽ continues to animate even four decades after his death.